Fear of monkeypox and intention to vaccinate against monkeypox: a network analysis - Caycho-Rodríguez, Tomás (2024)
ntroduction: The presence of fear of an infectious disease triggers psychological factors associated with perceived behavioral control over vaccination acceptance, subjective norms of vaccination acceptance, attitudes toward vaccination acceptance, and perceived infectiousness from disease. Objective: The study evaluated how symptoms of fear of Monkeypox specifically relate to intention to be vaccinated against Monkeypox in a sample of 506 Peruvian individuals with a mean age of 27.11 years (SD = 9.77). Methods: Participants responded to the Monkeypox Fear Scale (MFS) and a single item of Intention to be vaccinated against Monkeypox. Using network analysis, central fear symptoms and associations between symptoms and intention to vaccinate were identified. Results: The results suggest that the node with the highest centrality was item 5 of the MFS. Regarding the connection between the intention to be vaccinated and the MFS items, a direct relationship was observed with item 1 and an inverse relationship with item 6. In addition, the relationship between these MFS items and intention to vaccinate is higher in men compared to women. While it would be expected that a greater presence of symptoms of fear of Monkeypox could lead people to have a greater intention to be vaccinated against the disease, the results could lead other researchers to generate evidence to explain this relationship in other Latin American countries. Discussion: The evidence is useful for developing policies that favor vaccination against Monkeypox in Peru and other Latin American countries.